Lanthionine Synthetase C-Like 2 Modulates Immune Responses to Influenza Virus Infection - Leber, Andrew; Bassaganya-Riera, Josep; Tubau-Juni, Nuria; Zoccoli-Rodriguez, Victoria; Lu, Pinyi; Godfrey, Victoria; Kale, Shiv; Hontecillas, Raquel (Frontiers in Immunology, 2017)
Broad-based, host-targeted therapeutics have the potential to ameliorate viral infections without inducing antiviral resistance. We identified lanthionine synthetase C-like 2 (LANCL2) as a new therapeutic target for immunoinflammatory diseases. To examine the therapeutic efficacy of oral NSC61610 administration on influenza, we infected C57BL/6 mice with influenza A H1N1pdm virus and evaluated influenza-related mortality, lung inflammatory profiles, and pulmonary histopathology. Oral treatment with NSC61610 ameliorates influenza virus infection by down-modulating pulmonary inflammation through the downregulation of TNF-α and MCP-1 and reduction in the infiltration of neutrophils. NSC61610 treatment increases IL10-producing CD8+ T cells and macrophages in the lungs during the resolution phase of disease. The loss of LANCL2 or neutralization of IL-10 in mice infected with influenza virus abrogates the ability of NSC61610 to accelerate recovery and induce IL-10-mediated regulatory responses. These studies validate that oral treatment with NSC61610 ameliorates morbidity, mortality and accelerates recovery during influenza virus infection through a mechanism mediated by activation of LANCL2 and subsequent induction of IL-10 responses by CD8+ T cells and macrophages in the lungs.